Study on Dynamic Mechanical Properties of Full Tailings Cemented Backfilling Impacted by Cement-Sand Ratio - Shan Yang; Zhiyong Zhou; Yifei Zhao; Wei Yang (Advances in Civil Engineering)
In order to study the effect of cement-sand ratio on the dynamic mechanical properties of the full tailings cemented backfilling, three sets of full tailings cemented backfilling specimens with different cement-sand ratios were prefabricated. The uniaxial impact of the prefabricated specimens was performed by the Ф50 mm SHPB test system. Test results showed that full tailings cemented backfilling had strong reflection and damping effects on elastic wave propagation. At lower strain rates, specimens presented strength hardening, and at higher strain rates, the test specimens presented rapid-softening strength; the strength-hardened specimen reached the peak stress at 40 μs, and the softening specimen reached the peak stress at about 18 μs; with the increase of strain rate, dynamic compressive strength, growth factor of dynamic strength, peak strain, and dynamic-static strain ratio of specimens increased totally. When the cement-sand ratio increased, ultimate dynamic compressive strength, limit dynamic strength growth factor, and ultimate peak strain of the specimen were higher; at the same strain rate, with the increase of cement content, the dynamic compressive strength, dynamic strength growth factor, and dynamic-static strain ratio of the test piece all decreased. The failure mode of the specimen was crushing failure. Under the same strain rate, when the cement content decreased, there was a higher damage degree of specimens.